2022
DOI: 10.3390/molecules27175467
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Bioactivity of Microsorum scolopendria (Polypodiaceae): Antioxidant Effects on an Epithelial Damage Model

Abstract: Microsorum scolopendia (MS), which grows on the Chilean island of Rapa Nui, is a medicinal fern used to treat several diseases. Despite being widely used, this fern has not been deeply investigated. The aim of this study was to perform a characterization of the polyphenolic and flavonoid identity, radical scavenging, antimicrobial, and anti-inflammatory properties of MS rhizome and leaf extracts (RAE and HAE). The compound identity was analyzed through the reversed-phase high-performance liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
0
0
Order By: Relevance
“…Very few reports exist for the fern MS and a recent phytochemical study demonstrated their rich phenolics and flavonoid contents such as protocatechic acid, 4-O-glucoside, cirsimaritin, and isoxanthohumol. [9] Phenolics or polyphenolics as well as flavonoids are widely used in food industries, cosmetics pharmaceutics due to their antioxidant, antimicrobial, and anti-inflammatory activities. [10] [11] Importantly, metal ions coordination interaction with phenolic hydroxyl group-containing bio-organic molecules in natural plants is exploited for the preparation of important nanoparticles for drug delivery, bio-imaging, surface modification, and disease treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Very few reports exist for the fern MS and a recent phytochemical study demonstrated their rich phenolics and flavonoid contents such as protocatechic acid, 4-O-glucoside, cirsimaritin, and isoxanthohumol. [9] Phenolics or polyphenolics as well as flavonoids are widely used in food industries, cosmetics pharmaceutics due to their antioxidant, antimicrobial, and anti-inflammatory activities. [10] [11] Importantly, metal ions coordination interaction with phenolic hydroxyl group-containing bio-organic molecules in natural plants is exploited for the preparation of important nanoparticles for drug delivery, bio-imaging, surface modification, and disease treatment.…”
Section: Introductionmentioning
confidence: 99%